Review of Biopolymer Composite Through 3D Printing Techniques - Hamidie, Aiman Haiqal Aizam Hamidie; Adzila, Sharifah; Razak, Aisyah; Mat Isa, Najah (2025)
Since polymers are so important in our daily lives, 3D printing began with a polymer substrate for creating components. Aside from that, biopolymer composites have become popular due to their environmentally friendly, biodegradable, and biocompatible properties. Despite recent advances in 3D printing of biopolymer composites, this paper reviewed the printing technique of each biopolymer composite, which has a large number of printing techniques such as Fused Deposition Modelling (FDM), Selective Laser Sintering (SLS), Stereolithography (SLA), Ink Jet and others that can be used for biopolymer composite due to mechanical properties findings and application. These biopolymer composites are widely utilized in the biomedical field and are predicted to increase their benefits in this field, as well as FDM, which is the most regularly used 3D printing process.